Autonomy, practical rationality and being at one with oneself: a reply to Wendelborn. (1st November 2020) - Hand, Michael
ABSTRACT: In his belated reply to my 2006 article 'Against autonomy as an educational aim', Christian Wendelborn advances two objections to my argument and proposes two new candidates for an educational aim deserving of the name autonomy. I show here that his objections miss their mark and that neither of his new candidates is appointable.